2022
DOI: 10.1002/jcaf.22547
|View full text |Cite
|
Sign up to set email alerts
|

UK professional accounting bodies (PAB): Members’ unethical behaviors and exclusion

Abstract: Although previous studies have explored the disciplinary procedures and sanctions by PABs, the focus of these studies has often been generalized to all forms of infringements. This has prevented specific attention on the most severe ethical breaches by PAB members, that is, offences leading to exclusion. Consequently, we do not know their prevalence, the features of these behaviors or the motivating factors for their perpetration by members of the UK's PABs. Clarity on these issues is in the public interest gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Furthermore, the correlation test affirms a statistically significant correlation between the perception of compatriots, knowledge of ethics, and accountancy bodies. The findings are consistent with findings from similar studies by Jaijairam (2017b), Ishola et al (2018), Oboh et al (2020b), Yasseen et al (2020), and Adelopo and Meier (2022) who evidenced that a member of a professional accounting body influences the ethical behavior and professional conduct of accounting and finance professionals. For instance, a study conducted among professional accountants in Nigeria found that accountants who are members of an accounting body were more professional and ethical than those who were not (Ishola et al, 2018).…”
Section: Perception Of Compatriots (Pc)supporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the correlation test affirms a statistically significant correlation between the perception of compatriots, knowledge of ethics, and accountancy bodies. The findings are consistent with findings from similar studies by Jaijairam (2017b), Ishola et al (2018), Oboh et al (2020b), Yasseen et al (2020), and Adelopo and Meier (2022) who evidenced that a member of a professional accounting body influences the ethical behavior and professional conduct of accounting and finance professionals. For instance, a study conducted among professional accountants in Nigeria found that accountants who are members of an accounting body were more professional and ethical than those who were not (Ishola et al, 2018).…”
Section: Perception Of Compatriots (Pc)supporting
confidence: 92%
“…The findings are consistent with findings from similar studies by Jaijairam (2017b), Oboh et al (2020b), Yasseen et al (2020), and Adelopo and Meier (2022) that evidenced that professional accounting bodies have a firm stance on ethical behavior and conduct of their professional members. For instance, the study conducted among professional accounting bodies in the United Kingdom found that ethical misconduct and criminal conviction are the leading bases for membership expulsion and exclusion of accounting and finance professionals in the United Kingdom (Adelopo & Meier, 2022).…”
Section: Perception Of Compatriots (Pc)mentioning
confidence: 99%